INTERNALISASI PENDIDIKAN AGAMA ISLAM DALAM KONSEP AURAT DAN JILBAB DI ERA KONTEMPORER - Mohammad Usman (Ulumuna: Jurnal Studi Keilsman, 2020)
Islamic Religious Education is education that teaches students to understand Islamic-based lessons, which follow the teachings of the Koran and Al-Hadith. The model, style, and even the material provide a very strong factor in encouraging Muslim women to make the hijab an option in their clothing for their daily activities. the production of the hijab on a large scale as well as various kinds and even models, this is also what makes it attractive for young people, especially students in Islamic schools. Jilbab When following market tastes through the media with certain forms it is easily loved by young people so that it becomes a necessity, this kind of understanding in the realm of following fashion and slang has been very successful in influencing young people in expressing Islamic teachings by wearing a veil and of course according to individual tastes. If we examine the beginnings of veiling, veiling, veiling or the like, of course this does not originate from Islam, because long before Islam there was a concept of veiling in the Torah of the Jewish religion which had been introduced and also in the Christian Bible. And it is clarified of course in Islam with the instructions in the Al-quran and also a detailed and very detailed explanation by the scholars'. In Arabic vocabulary, we don't only find the word jilbab, but there are several vocabulary for covering the limbs such as veil, see, milhafah, libas. There are also clothes that cover specifically from the neck to the top of the khimar, niqab and burqu '. Etymologically, the word hijab comes from Arabic and the plural is Jalabib. This word is also written in the 30th Surah Al-Ahzab verse 59